Making Self-Consolidating Concrete Mixtures Using Waste Glass Micro-Particles (International Journal of Innovative Research in Engineering & Management, 2023)
As the pace of garbage production  worldwide is worrying. Among these waste items include  rubber, glass, wood goods, and plastic, among others.  Compared to other waste materials, glass garbage is  produced more often in India. However, approximately 60%  of glass trash is either disposed of in landfills or stored in  warehouses around the nation due to the low market value of  recycled glass and expensive transit costs. The chemical  inconsistencies among the many types of glasses, as well as  the difficulties in separating different coloured glasses, make  recycling challenging in addition to the existence of waste  products such plastic caps, metals, and paper. However, in  recent years it has become more difficult to replace coarse  aggregate, sand, and gravel with waste glass in concrete and  mortar. Since the 1960s, a number of researchers have  investigated the use of waste glass larger than 4.75 mm as a  coarse aggregate spare in concrete. There is a high need for  aggregate and clay (brick) sources in the manufacturing of  concrete. In 2015, 48.3 billion tonnes of aggregates were  used annually as building materials worldwide, with 2.2  billion tonnes of them being used in India. Waste resources  can be used as various types of construction material to get around the aggregate glass ultimatum. Only 45% of the 21  billion tonnes of glass trash produced in India in 2019 were  recycled, demonstrating the necessity for effective waste  glass procurement and management. This review provides  examples of how leftover glass may be used to make building  pieces. The study's primary goals are to learn more about the  physical and mechanical characteristics of waste glass-based  blocks and other products, to generate sustainable building  materials that can replace aggregates and clay, and to lessen  the amount of waste glass dumped in landfills.
Keywords: Aggregate; Cement; Concrete; Waste Glass